Success factors of regional airports: the case of Oporto airport - Carballo-Cruz, Francisco (2014)
Oporto Airport (OPO) is a success story among European regional airports. This success is expressed, among other ways, in the rapid expansion of routes and the strong growth in demand, as well as in the recognition of the airport’s quality by its users. Over the past decade, the volume of traffic increased by almost 3.4 million passengers, from the 2.6 million recorded in 2002 to over 6 million in 2012. In this paper, we analyse some of the factors that influenced the success of Oporto Airport, namely the expansion of capacity and improvements to infrastructure, the increase in the number of routes and the increased demand in response to the new capacities of this airport-airlines set. Particular emphasis is given to the role of low cost carriers (LCC) in the growth of Oporto Airport and to strategies of attracting more traffic. Some of the main opportunities and challenges that this airport will face in the coming years are also discussed.